A comparative macromorphological and ethnomedicinal analysis of five Kalanchoe Adans. Taxa from Bangladesh: Explore the comparative morphological profiling and ethnobotanical analysis of different ailments (Bangladesh Journal of Agriculture, 2023)
The best-known species of the succulents family Crassulaceae in Bangladesh are Kalanchoe blossfeldiana, Kalanchoe daigremonitnum, Kalanchoe heterophylla, Kalanchoe laciniata and Kalanchoe pinnata during the period January, 2019 to March, 2020. But this is the first time that two new species named K. delagoensis and K. gastonis-bonnieri were reported from Bangladesh in this study.Viviparous plantlets formation along the leaf margin is the remarkable feature of these new two species along with formerly reported species K. pinnata. The abundance of K. pinnata among the five species of this genus was the highest (53%), while K. gastonis-bonnieri was the lowest (3%). The experimented five species were used to treat 9 human ailments named cough and cold, cuts and wounds, stomach disorder, kidney and gall bladder stones, jaundice, high blood pressure, skin burning, headache, and eye pain. The citation frequency of all the species except K. laciniata ranged from 2% to 100% in contrast to any ailment, while K. blossfeldiana and K. pinnata were frequently cited. Alike citation frequency the species K. blossfeldiana and K. pinnata along K. gastonis-bonnieri had the highest fidelity level, but K. delagoensis had the lowest fidelity level among the five species analyzed. Leaf juice and baked leaf are the common modes of administration. The most cited and high-fidelity species K. blossfeldiana and K. pinnata were top-ranked in DMR analysis. These two top-ranked species are under threat for several factors and need conservation strategies.Bangladesh J. Agri. 2023, 48(1): 51-66